Perceived Factors Affecting Utilization of Traditional Birth Attendant in Moro Loval Government Area, Kwara State - Aibinuomo Ayomide Oluwaseyi; Titilope Olatorera Akinleye; Kolawole Abdulrahman Yahya; Ilori Oluwatosin Ruth; Mohammed Olatunji Bello; Jayeoba Olufunke Felicia; Ayinde Taiwo Oluwaseun (Journal of Science in Medicine and Life, 2023)
BACKGROUND: In Sub-Saharan Africa, inadequate maternal health services stand as a leading cause of women's mortality (Anyait et al., 2012). The use of unskilled home delivery poses a significant barrier to reducing maternal mortality (Oshonwoh et al., 2014), hindering the achievement of Sustainable Development Goal three, emphasizing good health and well-being. OBJECTIVE: This study aims to investigate the perceived factors influencing the utilization of traditional birth attendants among residents in the Malete community, Moro LGA, Kwara State. METHODS: A descriptive cross-sectional study involving 400 female residents of Moro LGA utilized a multi-stage sampling method. Seven communities in Moro Local Government Area, namely Elemere, Asomu, Shao, Olooru, Bode Saadu, Jebba, and Malete, were selected. In each of these communities, a few compounds were chosen using simple random techniques. Pregnant and non-pregnant women who had given birth within the last five years were recruited between July and August until the desired sample size was attained. RESULTS: Almost half of the respondents were aged 25-34 years, while another significant portion fell between 35-44 years old. The majority identified as Yoruba, with 4.8% being Hausa, and the remaining 7.5% belonging to other tribes. The majority (95.3%) practiced Islam, while 4.8% practiced Christianity. Regarding residence, 71.3% of respondents lived in rural areas, and 28.8% in urban/semi-urban areas. Nearly half (44.0%) had secondary education, while 25.5% and 11.8% had primary and tertiary education, respectively. In terms of monthly income, 42.8% earned less than 5000 monthly, and about one-third of husbands earned between 20,000-50,000. Occupationally, 36.8% were traders, 14.5% were housewives, and 21.3% were hairdressers. Only 14.0% of respondents were health insurance scheme cardholders. CONCLUSION: This study indicates that the majority of respondents were acquainted with someone who had utilized traditional birth attendants, emphasizing the perceived cost-effectiveness of these services. Respondents with lower socio-economic status tended to utilize traditional birth attendants more frequently. The study suggests a rising trend in the utilization of traditional birth attendants in rural communities, driven by increasing healthcare costs and unemployment rates. RECOMMENDATION: Policymakers and maternal health advocates should comprehend the factors contributing to the surge in maternal mortality rates and strive to formulate health policies addressing these issues. Additionally, funding agencies and non-governmental organizations (NGOs) can play a pivotal role by allocating funds to prioritize maternal health and offering financial support for this cause.